(untitled) (Bangladesh Journal of Otorhinolaryngology, 2022)
Background: Type 1 Tympanoplasty is a widely performed procedure for inactive mucosal COM. Considerable controversy remains in choice of type-1 tympanoplasty in the paediatric patients. Objectives: To assess the outcomes of type-1 tympanoplasty in paediatric patients. Methods: This study was conducted in the Department of Otolaryngology-Head & Neck Surgery, BSMMU, Dhaka, from July 2018 to December 2019, with 44 paediatric patients having an inactive mucosal variety of chronic otitis media. Patients were divided into 10-14 and 15-18 years age group. All patients underwent type-1 tympanoplasty under operating microscope and temporalis fascia used as a graft material. Minimum hearing improvement of 10 dB was regarded as an audiological success and an intact graft at the end of the third month was regarded as graft success. The statistical significance was set to p< 0.05. Results: The graft success rate was 90.9% and audiological improvement was 81.8% in paediatric tympanoplasty. Success rate was higher in 15-18 years age group than 10-14 years of age group which was statistically insignificant. Irrespective of the site, size, duration of discharge showed an insignificant association with outcomes of pediatric type-1 tympanoplasty. Conclusion: Type-1 tympanoplasty showed promising result in paediatric patients. The age of the patients did not significantly affect the postoperative outcome. Bangladesh J Otorhinolaryngol 2022; 28(1): 43-49